Från förorten till innerstaden och tillbaka igen - Jonas Lindbäck; Ove Sernhede (Educare)
The freedom to choose which school you want to attend in the Swedish school system can be understood as an opportunity to overcome the urban segregation. Each year there are pupils from the suburb of Beryd in Gothenburg, who choose to leave their suburb to attend an upper secondary school in the inner city. But several of these pupils choose to return to the upper secondary school in Beryd. The aim of this article was to study why these pupils choose to leave Beryd, and why they return. Through interviews with ten pupils at Berydsgymnasiet we examined how the shift between the suburb and the inner city raised questions concerning identity, place and belonging. The study shows how the pupils encounter with the inner city schools is connected with a strong feeling of alienation and non-belonging, an experience that is highly related to the segregated and hierarchically structured urban space.